Analysis Of Economic Structure In Sigi Regency For The Period 2009-2015 - Andi Heman Jaya (Jurnal Mantik, 2020)
The research used is descriptive research. To find out the economic growth in Sigi Regency using growth ratio model analysis (MRP) Economic structure in Sigi Regency using Location Quotion (LQ) analysis to find out the leading sectors using overlay analysis The results of the analysis of the 2000-2013 constant price Growth Ratio Model (MRP) show that the agricultural sector and the manufacturing sector are the fastest growing sectors. 2010 constant prices in 2014-2015 Wholesale and Retail Trade, and Car and Motorcycle Repair, information and communication sector, financial and insurance services sector, real estate sector, corporate services sector, government administration sector, defense and compulsory social security, health services and social activities. is the fastest growing sector. The results of the Location Quotient (LQ) analysis of GRDP in Sigi Regency at constant 2000 prices for the period 2009-2013, can be identified as the base sector, these two sectors are the base sector. The agricultural sector and the building sector. based on 2010 constant prices for the 2014-2015 period, in Sigi Regency the base sector in Sigi Regency is the agriculture, forestry and fishery sector. wholesale and retail trade in car and motorcycle repair, real estate, government administration, defense and compulsory social security, educational services.The results of the calculations from the two analytical tools after overlaying Sigi Regency constant prices 2000 years 2009-2013. The priority sector is the agricultural sector. which have the potential to be developed in the manufacturing sector, the electricity, gas and clean water sector, the hotel and restaurant trade sector, and the services sector. The sector under pressure in Sigi Regency is the construction sector. the transportation and communications sector, the financial sector, leasing and corporate services. sectors that are still lagging behind in Sigi Regency. 2010 constant prices for 2014-2015 priority sectors of agriculture, forestry, and fisheries, water supply, waste management and recycling, wholesale and retail trade; car and motorcycle repair, real estate, government administration, defense and compulsory social security, educational services, potential sectors namely, electricity and gas procurement, transportation and warehousing, provision of accommodation and food and drink, information and communication, financial services and insurance, corporate services, health services and social activities, other services. The lagging sectors are the mining and quarrying sector, processing industry, construction.